2013
DOI: 10.1371/journal.pone.0057685
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stimulus-Induced Gamma Activity in Humans during Propofol-Induced Sedation

Abstract: Stimulus-induced gamma oscillations in the 30–80 Hz range have been implicated in a wide number of functions including visual processing, memory and attention. While occipital gamma-band oscillations can be pharmacologically modified in animal preparations, pharmacological modulation of stimulus-induced visual gamma oscillations has yet to be demonstrated in non-invasive human recordings. Here, in fifteen healthy humans volunteers, we probed the effects of the GABAA agonist and sedative propofol on stimulus-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 64 publications
8
51
0
Order By: Relevance
“…More recently, comparable results were obtained with the NMDA receptor antagonist ketamine [Shaw et al, 2015]. In addition to the frequency modulation, these studies found increased amplitude of gamma responses with GABAergic enhancement, replicating previous results obtained with administration of the GABA A agonist propofol [Saxena et al, 2013]. Increased gamma amplitude accompanying a shift toward lower gamma frequencies may be related to the recruitment of larger pyramidal cell populations achieved under longer periods of inhibition [Gonzalez‐Burgos and Lewis, 2012].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…More recently, comparable results were obtained with the NMDA receptor antagonist ketamine [Shaw et al, 2015]. In addition to the frequency modulation, these studies found increased amplitude of gamma responses with GABAergic enhancement, replicating previous results obtained with administration of the GABA A agonist propofol [Saxena et al, 2013]. Increased gamma amplitude accompanying a shift toward lower gamma frequencies may be related to the recruitment of larger pyramidal cell populations achieved under longer periods of inhibition [Gonzalez‐Burgos and Lewis, 2012].…”
Section: Discussionsupporting
confidence: 83%
“…For example, the GABA A positive allosteric modulator propofol was found to increase gamma amplitude, but left gamma frequency unchanged [Saxena et al, 2013]. More surprisingly, a recent study reported that neither the amplitude nor the frequency of visual gamma responses were modulated by tiagabine [Muthukumaraswamy et al, 2013a], a drug that prolongs IPSC duration by selectively inhibiting the re‐uptake of GABA from the synapse.…”
Section: Introductionmentioning
confidence: 99%
“…Muthukumaraswamy and colleagues (26) found that elevation of extracellular GABA levels by tiagabine, which blocks GABA reuptake, did not modulate gamma oscillations in either visual or motor cortex. Finally, Saxena and colleagues (27), using GABA-A agonist propofol, observed an increase in stimulus-induced gamma amplitude only. Taken together, none of these studies provides support for a measurable relationship between GABA levels and visual gamma frequency in the human brain.…”
Section: Discussionmentioning
confidence: 96%
“…In line with the role of inhibitory interneurons in generating gamma band activity, a positive correlation between GABA levels in superior temporal sulcus (measured using MRS) and the power of induced gamma band oscillations has been reported (Balz et al, 2016), suggesting that increased induced gamma band power is associated with higher GABA levels. This position is also supported by pharmalogical manipulations of GABA, as administration of propofol (a GABA agonist) leads to an increase in induced gamma band power (Saxena, Muthukumaraswamy, & Diukova, 2013). However, other studies have not found any association between GABA levels (in occipital cortex) and induced gamma band power (Cousijn et al, 2014;Muthukumaraswamy, Edden, Jones, Swettenham, & Singh, 2009).…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 92%
“…Peak gamma frequency has been shown to be stable over time, and also to be highly heritable (van Pelt, Boomsma, & Fries, 2012), therefore peak gamma frequency may represent a more useful way to investigate E/I balance in human participants. Some studies have shown that visuallyinduced peak gamma frequency is correlated with resting GABA levels in occipital cortex Gaetz, Edgar, Wang, & Roberts, 2011;Muthukumaraswamy et al, 2009) although others have failed to replicate this relationship (Cousijn et al, 2014;Saxena et al, 2013). The technical difficulty in measuring GABA concentration in vivo with MRS and the different scan parameters used in these studies may contribute to the lack of convergence in results, Nevertheless, peak gamma frequency elicited by visual stimuli has been found to be higher in ASD (Dickinson et al, 2016), and correlated with autistic traits in the neurotypical population (Dickinson, Bruyns-Haylett, Jones, & Milne, 2015).…”
Section: High Frequency Neural Oscillations (Gamma-band Activity)mentioning
confidence: 99%